A probiotic lozenge administered medical device and its effect on salivary mutans streptococci and lactobacilli - ESBER ÇAGLAR, OZGUR ONDER KUSCU, SULE KAVALOGLU CILDIR, SENEM SELUI KUVVETLI (IAPD and Blackwell, 2008)
Probiotics are food supplements that contain live bacteria, which benefit people’s digestive tract by maintaining a balanced gut flora 1–4 . The beneficial role of Lactobacillus reuteri ATCC 55730 in general health, immunomodulation, and disease protection has been observed and described in a number of studies 5–7 . Within dentistry, there are only a few studies investigating the effect of L. reuteri in the oral cavity. However, the effect of L. reuteri on one of the caries pathogens has been evaluated in vitro by Nikawa et al . 8 , and consumption of yogurt containing L. reuteri SD 2112 (ATCC 55730) resulted in a significant growth inhibition of Streptococcus mutans , which was in contrast with other probiotic lactobacilli strains.